PENERAPAN PROJECT BASED LEARNING SEBAGAI UPAYA STRATEGIS PENGEMBANGAN SEKOLAH KEJURUAN - Akhyar, Muhammad (Jurnal Inovasi Pendidikan, 2007)
Nowadays, schools could not rely on the government contribution any more. Even though the government, Depdiknas in this case, recommended that the schools should develop themselves based on their capabilities through schoolbased management. In accordance with the recommendation above, projectbased learning is an alternative learning model for developing vocational education. The model can give the vocational education several benefits such as economical benefit, educational benefit and social benefit. Economical benefits can be used for developing the project as well the school. Educational benefits consist of knowledge, skill, the ability of interacting intelectually, emotionally and socially of the students. Students employed in the project can receive certain salary that can be used to support their life and educational needs. The leader of the school plays an important role to maintain the sustain ability of applying the model. He should develop networks concerning with relevant projects. The sustain ability of applying the model does not only depend on the role of the leader of the school but also depend on the calculation of the benefit economically and government policy. The learning model will be sustainable if the project is beneficial.